Vyacheslav Vs. Ivanov (1929-2017) - Vine, Brent; Yakubovich, Ilya (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
A year ago, the academic world received the tragic news about the death of the Russian polymath and cultural public figure Vyacheslav Vsevolodovich Ivanov. Few people are qualified to appreciate all the facets of his talent and the full range of his contributions. In this review we shall concentrate on Ivanov’s impact on the field of Indo-European Studies and, secondarily, other aspects of linguistics. Nevertheless, since the accomplishments of the deceased can hardly be separated from his unique personality, we will pay particular attention to the Sitz im Leben of his academic work.